Assessment of knowledge, attitude and practice of pediatrics regarding hospital dentistry in Isfahan province - Alireza Eshghi; Arezoo Pirhaji; Firoozeh Nilchian (Tehran University of Medical Sciences, 2021)
Background and Aims: A significant percentage of children with dental caries require, hospital dentistry and their parents do not have much information in this regard. The aim of this study was to determine the knowledge, attitude and practice of pediatricians in hospital dentistry in Isfahan Province. Materials and Methods: This cross-sectional study was performed on 100 pediatricians working in Isfahan. The self-administered questionnaire included demographics of doctors and 19 questions for assessing the knowledge, attitude and practice of pediatric practitioners about hospital dentistry under general anesthesia. Raw data were analyzed by Chi-square test using SPSS software version 23. Results: 100 pediatricians with an average age of 44.1±5.7 years (57% male) completed the questionnaire. 53% of the pediatricians had a high level of awareness about hospital dentistry and 42% about its related guides. 66% practitioners had a favorable attitude toward general anesthesia and costs, while 71% considered the parentschr('39') awareness were poor about hospital dentistry. Only 43% of pediatricians performed oral examinations in their daily visits, and 17% had a referral for hospital dentistry. Male pediatricians aged from 35 to 45 had a higher level of knowledge about hospital dentistry. The attitude and practice of pediatricians did not have a significant relationship with their age. Meanwhile, male pediatricians had better performance in oral and dental examination and referral for hospital dentistry (P=0.15). Conclusion: From the results of this study, there is a need for a serious improvement in the level of knowledge, attitude, and practice of pediatricians in the field of hospital dentistry.